PEMANFAATAN KAWASAN BUKIT PAYANG SEBAGAI DAYA TARIK WISATA ALAM DI KECAMATAN KINTAMANI, KABUPATEN BANGLI - I Kadek Markayasa; Ida Bagus Suryawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2015)
ABSTRACT Payang Hill is a Hilly area that has been the potential of tourism in the Batur Tengah Village. Payang Hill already begin tourists visited in 2010, with the number of tourists still slightly. Potency resources of the still quite natural, so it become a tourist atrraction. The research is oriented at kronowlge the use and potency of the Payang Hill as a natural tourist atrracton in district of Kintamani, Expected to be able provide and answer the problem formulation, what the potency of the regional as Payang Hill natural atrractions and how the utilization of the regional as Payang Hill natural atrractions. This study uses primary and secondary data sources, whereas the type of data used is also quantitative, and qualitative data. Collecting data through observation, interviews, documentation, and library research. Descriptive analysis of qualitative. The result of the research : 1) Payang Hill can be developed into a tourist attraction, because it has the potencies such as natural, cultural, and education. 2) Payang Hill already to implimentation to use the potency with how to package and create a means of support for tourism activities for tourist.